1974
DOI: 10.1042/cs048081s
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plasma Renin Activity and Blood Pressure after Acute and Chronic Administration of β-Adrenergic Receptor-Blocking Drugs

Abstract: 1.Prindolol and propranolol chronically cause a fall in mean blood pressure and mean plasma renin activity, but no correlation was observed between the two variables.2. The response of blood pressure to prindolol and propranolol was not predicted by the basal plasma renin activity.3. Propranolol administered acutely caused the plasma renin activity to fall with no acute change in blood pressure, whereas prindolol caused the blood pressure to fall with no change in plasma renin activity.4. The effects of 8-adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…This, however, is not the case, although it is in no way excluded that primary essential hypertension may induce renal lesions with the consequence that the hypertension becomes renin dependent. The hypothesis of a relationship between PRA and the blood pressure-lowering effect of ,8-adrenergic blockers has aroused quite some interest, but only a few investigators have confirmed the original findings, whereas the majority found no such relationship (STOKES et al, 1974;BRAVO et al, 1975;MORGAN et al, 1975). In more recent studies it was observed that in patients with essential hypertension and a low PRA, higher doses of ,8-adrenergic blockers were necessary than in patients with normal or high PRA (KAPLAN, 1975;SHAND et al, 1975;HOLLIFIELD et al, 1976).…”
Section: Idealmentioning
confidence: 90%
“…This, however, is not the case, although it is in no way excluded that primary essential hypertension may induce renal lesions with the consequence that the hypertension becomes renin dependent. The hypothesis of a relationship between PRA and the blood pressure-lowering effect of ,8-adrenergic blockers has aroused quite some interest, but only a few investigators have confirmed the original findings, whereas the majority found no such relationship (STOKES et al, 1974;BRAVO et al, 1975;MORGAN et al, 1975). In more recent studies it was observed that in patients with essential hypertension and a low PRA, higher doses of ,8-adrenergic blockers were necessary than in patients with normal or high PRA (KAPLAN, 1975;SHAND et al, 1975;HOLLIFIELD et al, 1976).…”
Section: Idealmentioning
confidence: 90%
“…In the absence of these DNA markers, the first approach to the case control analysis was to select Candidate genes based on their function and compare their frequency in cases versus controls. Studies reported over 100 candidates associated with genetic predisposition for CAD (18), (19), of which almost none would be confirmed in subsequent studies.…”
Section: Development Of the Technology To Pursue Genome Wide Associatmentioning
confidence: 93%
“…The association of rising BP and PRA despite rising doses of pindolol does not necessarily imply a cause and effect relationship. Such a relationship between antihypertensive and PRA-lowering effect of P-adrenergic blocking drugs has been claimed by some investigators (4, 5 , 18) and denied by others (1,9,10). In this study, changes in PRA and BPs were not significantly correlated.…”
Section: Resultsmentioning
confidence: 87%
“…reduction of PRA (2,15). Changes in PRA during pindolol treatment were not correlated with the antihypertensive drug response (2,8,9,10,15).…”
mentioning
confidence: 97%